2020
DOI: 10.1177/2332858419897886
|View full text |Cite
|
Sign up to set email alerts
|

Early Efficacy of Multitiered Dual-Language Instruction: Promoting Preschoolers’ Spanish and English Oral Language

Abstract: The purpose of this cluster randomized group study was to investigate the effect of multitiered, dual-language instruction on children’s oral language skills, including vocabulary, narrative retell, receptive and expressive language, and listening comprehension. The participants were 3- to 5-year-old children (n = 81) who were learning English and whose home language was Spanish. Across the school year, classroom teachers in the treatment group delivered large-group lessons in English to the whole class twice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 55 publications
0
40
0
1
Order By: Relevance
“…For younger students, language interventions have been contextualized by teaching vocabulary, grammar, and syntax in storybooks, biweekly themes, and storytelling activities. [97][98][99] For older students, a contextualized intervention session might target complex syntax, morphological knowledge, and inferencing strategies using a passage from the student's social studies textbook. In contrast, a discrete skill intervention would involve targeting individual language skills in a series of unrelated activities.…”
Section: Language Intervention Contextualized In the Academic Curriculummentioning
confidence: 99%
“…For younger students, language interventions have been contextualized by teaching vocabulary, grammar, and syntax in storybooks, biweekly themes, and storytelling activities. [97][98][99] For older students, a contextualized intervention session might target complex syntax, morphological knowledge, and inferencing strategies using a passage from the student's social studies textbook. In contrast, a discrete skill intervention would involve targeting individual language skills in a series of unrelated activities.…”
Section: Language Intervention Contextualized In the Academic Curriculummentioning
confidence: 99%
“…Although several narrative interventions have employed storybooks (Adlof et al, 2014;Brinton & Fujiki, 2017;Catts et al, 2016;Petersen et al, 2010), some researchers (including us) have strategically designed stories for initial intensive and targeted narrative practice (Brown et al, 2014;Favot et al, 2018;Hayward & Schneider, 2000;Petersen et al, 2014;Spencer et al, 2020, Spencer, Petersen, & Adams, 2015Spencer & Slocum, 2010;Swanson et al, 2005). Some advantages of using prepared stories (over storybooks) for narrative intervention include being able to control what structures, vocabulary, and complex language children are exposed to, easily teaching metalinguistics through multiple exemplar training and rapid practice cycles within session because stories are brief, and building narrative comprehension and production simultaneously.…”
Section: Use Multiple Exemplars To Promote Metalinguistics and Generalizationmentioning
confidence: 99%
“…Therefore, we recommend fading pictures and illustrations before icons so that children can benefit from a smooth and gradual transition from easy to difficult tasks within a session. For example, in recent studies featuring small group narrative intervention with Spanish-speaking preschoolers learning English (Spencer et al, , 2020, illustrations and icons were displayed while the story was modeled and when the first child retold the story independently. When the second child retold the story independently, only the icons were available, and when the third child retold the story, no visuals were available.…”
Section: Use Visual Support To Make Abstract Concepts Concretementioning
confidence: 99%
“…With a targeted interest on enhancing dual language Spanish-speaking preschoolers' language comprehension, T. D. Spencer et al (2020) anchor their study on investigating the effect of multitiered, Spanish-English instruction for students attending Head Start in the Southwest United States, a long-serving EL region. Results of the cluster randomized group study revealed positive effects on students' narrative language skills in English, which is not to be underestimated as these children were selected on the basis of evidencing below-age expectations on English measures.…”
Section: The Understudied Role Of Language Comprehensionmentioning
confidence: 99%
“…With a targeted interest on enhancing dual language Spanish-speaking preschoolers’ language comprehension, T. D. Spencer et al (2020) anchor their study on investigating the effect of multitiered, Spanish-English instruction for students attending Head Start in the Southwest United States, a long-serving EL region.…”
Section: The Understudied Role Of Language Comprehensionmentioning
confidence: 99%